Revealing Power Relations in Online Learning: A Critical Classroom Discourse Analysis - Fajar, Muh; Nadhillah, Farah (English Education:Journal of English Teaching and Research, 2023)
The Government of Indonesia has made policy by implementing learning with online system through several online platforms since the pandemic covid_19 in 2020. The lecturers and the students of English Department of STKIP PGRI Jombang as unseperated parts of the higher education in Indonesia must realize this policy. Of the reasons, this research will employ qualitative reserach by adopting the theory of politeness and supported by the theory of critical classroom discourse analysis (CCDA), thus, it is aimed at investigating how power relation between the lecturer and the students of English Department of STKIP PGRI Jombang can maintain their good social relations. This research will be conducted to analyze the politeness strategy used by lecturer and students on online learning process. This research will explore what politeness strategy the lecturer apply to the students, what word choice the lecturer use in applying the politeness strategy toward the students and why the lecturer apply the politeness strategy to the students on online learning. The research, furthermore, will relate relate the examination of politeness and critical classroom discourse analysis to get true data analysis of the research. The findings showed that a lecturer maintains good manners to his students so that even though the position of a lecturer is higher, it is different from his students, which has a different role as a consequence. There were three stages of uncovering their power relations. The first stage, this research employed the lecturer’s dominant role to determine the construction of power to his students. It could be described in the analysis of the conversation related to the greetings in the initial of each meeting in online learning and the preparation of group discussion. The second stage, the researcher explored the solidarity expressed the lecturer to his students by employing his personal experiences and his expression of his sorry to hear when there was a student’s father was sick. Those two stages played important roles of exposing their relationship both equal and unequal. The lecturer exercised his power indicated that their social relations are unequal. On the contrary, the solidarity exposed by the lecturer to his students indicated that their social relations are equal.